HISTOLOGIC PICTURE OF BEEF DIGESTED BY PAYA PAPAIN ENZYME - Yatri Drastini (Jurnal Sain Veteriner, 1999)
The study was conducted to show the histologic picture of beed digested by different concentration of PAYA papain enzyme. Twenty pieces of beed of m. femoralis, 1 x 0.5 x 0.5 cm in size, were allocated into four groups. Group I was injected with aquadest as control; group II, III, dan IV were injected with PAYA 0.25%, 0.50%, and 0.75% of the weight of meat, respectively. The samples were heated in a waterbath 65°C to activate the enzyme for 0, 15, 30, 45, and 60 minutes. Samples were then put into 10% formalin solution to stop the enzyme. The were stained with haematoxyline-eosine (HE) for histologic picture. The result shows PAYA papain enzyme starts to disintegrate myofibril in the concentration of 0.50% for 30 minutes. The higher is the concentration, the more do changes of myofibril take place in the form of inflamation, disintegration, and lysis.